2
$\begingroup$

I am trying to learn how to parallel transport a vector $V^\alpha=(V^\theta_0,V^\phi_0)=\text{constant}$ on the surface of a sphere of radius $R$, starting from $(R,0,0)$ to $(R,\pi/2,0)$ along the line $\phi=0$. The coordinates, therefore are, $x^\alpha=(R,\theta(\lambda),0)$, where $\lambda$ is the parameter along the path. Using the condition of parallel transport, $$ \frac{dV^\alpha}{d\lambda} = -\Gamma_{\beta\nu}^{\alpha}V^\nu\frac{dx^\beta}{d\lambda} $$ After solving the equation of parallel transport I get the following differential equations, $$ \frac{dV^\theta}{d\lambda}=0 $$ $$ \frac{dV^\phi}{d\lambda}=-\frac{\cos \theta}{\sin \theta}V^\phi $$ The $V^\theta$ equation is simple, it just says $V^\theta = \text{constant}$. I am confused about the other equation. The solution is, $$ \ln V^\phi=-\ln \sin \theta + C $$ $$ V^\phi \sin \theta = C $$ Here, $C$ is the constant of integration. When I put the initial conditions $V^\alpha=(V^\theta_0,V^\phi_0)$ at $(R,0,0)$, $C$ just comes out to be zero which implies that $V^\phi$ is zero always, since $\sin \theta(\lambda)$ cannot be zero along the entire path which basically also means that $V^\phi_0=0$.

I do not know how to make sense of this result. I am trying to complete a "triangle" of great circles along the sphere going from $(R,0,0) \rightarrow (R,\pi/2,0) \rightarrow (R,\pi/2,\pi/2)\rightarrow (R,0,\pi/2)$.

$\endgroup$
2
  • $\begingroup$ Remember that $\theta$ is a given function of $\lambda$. You need to put that in the equation for $V^\phi$. $\endgroup$
    – Javier
    Jul 5, 2018 at 13:39
  • $\begingroup$ I did. That is how I got the solution $V^\phi \sin \theta = C$. $\endgroup$
    – Shaz
    Jul 5, 2018 at 18:24

2 Answers 2

3
$\begingroup$

The problem is that the coordinates are not well defined at the north pole. There's no way to have a $\phi$ component there; you can only have a $\theta$ component, but that doesn't tell you the direction of the vector. Distinguishing $(R,0,0)$ and $(R, 0, \pi/2)$ also doesn't makes sense, they're the same point.

To avoid this problem, you could for example translate your triangle so it covers $\pi/4 < \theta < 3\pi/4$, or use stereographic coordinates or any other coordinate system that is well behaved at the pole.

$\endgroup$
3
  • $\begingroup$ Yes, I figured it must have something to do with the singularity. Couldnt quite place what though. Thanks. I did somewhat you suggest but I am just taking a triangle at an arbitrary location keep $\theta$ constant on the base and the sides are at $\phi = \text{constant}$. Thanks a bunch. $\endgroup$
    – Shaz
    Jul 6, 2018 at 4:59
  • $\begingroup$ So my equations are rather complicated by the fact that I did not take numerical values of the coordinates of the sides of the triangle. When I compare the initial vector with the final vector (to measure the angle by taking the dot product) I get a rather complicated equation which depends on the $(R, \theta, \phi)$ of the corners. I guess that is acceptable because the difference in the angle of the initial and the transported vector should depend on the size of the triangle (coordinates of the corners). Right? $\endgroup$
    – Shaz
    Jul 6, 2018 at 7:02
  • $\begingroup$ @Shaz I don't know the answer off the top of my head, but that sounds reasonable. $\endgroup$
    – Javier
    Jul 6, 2018 at 11:18
0
$\begingroup$

REFERENCE : My answer here What is the drawing scheme of the parallel transport of a vector?. $=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=$

enter image description here See a 3d view of Figure-01 here

Your path of parallel transport is arc of a meridian (a great circle) from the north pole to a point in the equator, see points $\boxed{\boldsymbol{0}},\boxed{\boldsymbol{1}},\boxed{\boldsymbol{2}}$ in Figure-01. That is the vector is transported along a geodesic. This means that it keeps its angle with respect to the geodesic path and its magnitude unchanged. So the components $\mathbf{V}^{\boldsymbol{\theta}}$ and $\mathbf{V}^{\boldsymbol{\phi}}$, that is the projections of $\mathbf{V}$ on the axes $\mathbf{e}_{\boldsymbol{\theta}}$ and $\mathbf{e}_{\boldsymbol{\phi}}$ respectively of the local coordinate system are unchanged. You have found that $\mathbf{V}^{\boldsymbol{\theta}}\boldsymbol{=}\texttt{constant}$. It's all right. But you must find also that $\mathbf{V}^{\boldsymbol{\phi}}\boldsymbol{=}\texttt{constant}$. So, something is going wrong with your differential equation with respect to $\phi$. You must check it.

$=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=$

ADDENDUM :

enter image description here

I think that to avoid the singularities of the north pole you may equivalently well transport the vector along the path $\boxed{\boldsymbol{0}},\boxed{\boldsymbol{1}},\boxed{\boldsymbol{2}}$ on the equator as shown in Figure-02 and after that place the north pole on point $\boxed{\boldsymbol{0}}$ (since no-one knows where is your north pole from the beginning).

The parametric equation of this $90^\circ$-arc with parameter the angle $\phi$ is \begin{equation} \require{cancel} \boldsymbol{\chi}\left(\phi\right)\boldsymbol{=}\left[\:\chi^{\theta}\left(\phi\right)\,,\chi^{\phi}\left(\phi\right)\vphantom{\dfrac{a}{b}}\right]\boldsymbol{=}\left[\:\theta_{0}\,,\frac{\pi}{2}\boldsymbol{-}\phi\right]\boldsymbol{=}\left[\frac{\pi}{2}\,,\frac{\pi}{2}\boldsymbol{-}\phi\right]_{\phi=0}^{\phi=\tfrac{\pi}{2}} \tag{01}\label{01} \end{equation}

Now consider that at point $\boxed{\boldsymbol{0}}$ we have a vector on the tangent plane \begin{equation} \mathbf{V}_0\boldsymbol{=} \begin{bmatrix} V^\theta_0 \vphantom{\dfrac{a}{b}}\\ V^\phi_0 \vphantom{\dfrac{\tfrac{a}{b}}{b}} \end{bmatrix} \tag{02}\label{02} \end{equation} which we want to parallel transport along the arc to point $\boxed{\boldsymbol{2}}$.

For the parallel transport we use the equation provided by the OP \begin{equation} \frac{\mathrm dV^\alpha}{\mathrm d\phi} \boldsymbol{=} \boldsymbol{-}\Gamma_{\beta\nu}^{\alpha}V^\nu\frac{\mathrm d\chi^\beta}{\mathrm d\phi} \qquad \left(\alpha,\beta,\nu \boldsymbol{=}\theta,\phi\right) \tag{03}\label{03} \end{equation} where $\Gamma_{\beta\nu}^{\alpha}$ the Christoffer symbols. Above equation could be expressed as \begin{equation} \dfrac{\mathrm d\mathbf{V}}{\mathrm d\phi} \boldsymbol{=} \begin{bmatrix} \dfrac{\mathrm dV^\theta}{\mathrm d\phi}\vphantom{\dfrac{a}{\dfrac{a}{b}}}\\ \dfrac{\mathrm dV^\phi}{\mathrm d\phi}\vphantom{\dfrac{a}{b}} \end{bmatrix} \boldsymbol{=}\boldsymbol{-} \begin{bmatrix} \Bigl< \boldsymbol{\Gamma^{\theta}}\mathbf{V},\dfrac{\mathrm d\boldsymbol{\chi}}{\mathrm d\phi}\Bigr> \vphantom{\dfrac{a}{\dfrac{a}{b}}}\\ \Bigl< \boldsymbol{\Gamma^{\phi}}\mathbf{V},\dfrac{\mathrm d\boldsymbol{\chi}}{\mathrm d\phi}\Bigr> \vphantom{\dfrac{a}{\dfrac{a}{b}}} \end{bmatrix} \tag{04}\label{04} \end{equation} where from \eqref{01} \begin{equation} \dfrac{\mathrm d\boldsymbol{\chi}}{\mathrm d\phi}\boldsymbol{=}\dfrac{\mathrm d}{\mathrm d\phi} \begin{bmatrix} \chi^{\theta}\left(\phi\right)\vphantom{\dfrac{a}{\dfrac{a}{b}}}\\ \chi^{\phi}\left(\phi\right)\vphantom{\dfrac{a}{\tfrac{a}{b}}} \end{bmatrix} \boldsymbol{=}\dfrac{\mathrm d}{\mathrm d\phi} \begin{bmatrix} \dfrac{\pi}{2}\vphantom{\dfrac{a}{\dfrac{a}{b}}}\\ \dfrac{\pi}{2}\boldsymbol{-}\phi\vphantom{\dfrac{a}{\tfrac{a}{b}}} \end{bmatrix} \boldsymbol{=}\boldsymbol{-} \begin{bmatrix} \:\:0\:\:\vphantom{\dfrac{a}{\dfrac{a}{b}}}\\ \:\:1\:\:\vphantom{\dfrac{a}{\tfrac{a}{b}}} \end{bmatrix} \tag{05}\label{05} \end{equation} and $\boldsymbol{\Gamma^{\theta}},\boldsymbol{\Gamma^{\phi}}$ the following matrices of Christoffer symbols \begin{align} \boldsymbol{\Gamma^{\theta}}\boldsymbol{=}\Gamma^{\theta}_{\beta\nu}& \boldsymbol{=} \begin{bmatrix} \: \Gamma^{\theta}_{\theta\theta} & \hphantom{=}\Gamma^{\theta}_{\theta\phi} \:\vphantom{\dfrac{a}{b}}\\ \: \Gamma^{\theta}_{\phi\theta} & \hphantom{=}\Gamma^{\theta}_{\phi\phi} \:\vphantom{\dfrac{a}{b}} \end{bmatrix} \tag{06a}\label{06a}\\ \boldsymbol{\Gamma^{\phi}}\boldsymbol{=}\Gamma^{\phi}_{\beta\nu}& \boldsymbol{=} \begin{bmatrix} \: \Gamma^{\phi}_{\theta\theta} & \hphantom{=}\Gamma^{\phi}_{\theta\phi} \:\vphantom{\dfrac{a}{b}}\\ \: \Gamma^{\phi}_{\phi\theta} & \hphantom{=}\Gamma^{\phi}_{\phi\phi} \:\vphantom{\dfrac{a}{b}} \end{bmatrix} \tag{06b}\label{06b} \end{align} The Christoffer symbols are expressed through the components of the metric tensor $\mathbf{g}$ \begin{equation} \Gamma_{\beta\nu}^{\alpha}\boldsymbol{=} \frac{1}{2}\sum\limits_{k\boldsymbol{=}\theta,\phi} g^{\alpha k} \left(\frac{\partial g_{k\nu}}{\partial \chi^{\beta }}\boldsymbol{+}\frac{\partial g_{\beta k}}{\partial \chi^{\nu}}\boldsymbol{-}\frac{\partial g_{\beta \nu}}{\partial \chi^{k}}\right) \tag{07}\label{07} \end{equation} From the infinitesimal displacement on the sphere \begin{equation} \left(\mathrm ds\right)^2\boldsymbol{=}R^2\left(\mathrm d\theta\right)^2\boldsymbol{+}R^2\sin^2\theta\left(\mathrm d\phi\right)^2 \tag{08}\label{08} \end{equation} the metric tensor is \begin{align} \mathbf{g}\boldsymbol{=}g_{ij}& \boldsymbol{=} \begin{bmatrix} \: g_{\theta\theta} & \hphantom{=}g_{\theta\phi} \:\vphantom{\dfrac{a}{b}}\\ \: g_{\phi\theta} & \hphantom{=}g_{\phi\phi} \:\vphantom{\dfrac{a}{b}} \end{bmatrix} \boldsymbol{=} \begin{bmatrix} \hphantom{r^2}R^2\hphantom{r^2\theta} & \hphantom{r^2}0\hphantom{r^2\theta} \vphantom{\dfrac{a}{b}}\\ \hphantom{r^2}0\hphantom{r^2\theta} & R^2\sin^2\theta \vphantom{\dfrac{a}{b}} \end{bmatrix} \tag{09a}\label{09a}\\ \mathbf{g}^{\boldsymbol{-}1}\boldsymbol{=}g^{ij}& \boldsymbol{=} \begin{bmatrix} \: g^{\theta\theta} & \hphantom{=}g^{\theta\phi} \:\vphantom{\dfrac{a}{b}}\\ \: g^{\phi\theta} & \hphantom{=}g^{\phi\phi} \:\vphantom{\dfrac{a}{b}} \end{bmatrix} \boldsymbol{=} \begin{bmatrix} \hphantom{r^2}R^{\boldsymbol{-}2}\hphantom{r^2\theta} & \hphantom{r^2}0\hphantom{r^2\theta} \vphantom{\dfrac{a}{b}}\\ \hphantom{r^2}0\hphantom{r^2\theta} & R^{\boldsymbol{-}2}\sin^{\boldsymbol{-}2}\theta \vphantom{\dfrac{a}{b}} \end{bmatrix} \tag{09b}\label{09b} \end{align} So for the elements of $\boldsymbol{\Gamma^{\theta}}$ \begin{align} \Gamma^{\theta}_{\theta\theta} & \boldsymbol{=} \frac12\left[g^{\theta\theta} \left(\cancelto{0}{\frac{\partial g_{\theta\theta}}{\partial \theta}}\boldsymbol{+}\cancelto{0}{\frac{\partial g_{\theta\theta}}{\partial \theta}}\boldsymbol{-}\cancelto{0}{\frac{\partial g_{\theta\theta}}{\partial \theta}}\right)\boldsymbol{+} \cancelto{0}{g^{\theta\phi}} \left(\frac{\partial g_{\phi\theta}}{\partial \theta}\boldsymbol{+}\frac{\partial g_{\theta\phi}}{\partial \theta}\boldsymbol{-}\frac{\partial g_{\theta\theta}}{\partial \phi}\right)\right]\boldsymbol{=}0 \tag{10a}\label{10a}\\ \Gamma^{\theta}_{\theta\phi} & \boldsymbol{=} \frac12\left[g^{\theta\theta} \left(\cancel{\frac{\partial g_{\theta\phi}}{\partial \theta}}\boldsymbol{+}\cancelto{0}{\frac{\partial g_{\theta\theta}}{\partial \phi}}\boldsymbol{-}\cancel{\frac{\partial g_{\theta\phi}}{\partial \theta}}\right)\boldsymbol{+} \cancelto{0}{g^{\theta\phi}} \left(\frac{\partial g_{\phi\phi}}{\partial \theta}\boldsymbol{+}\frac{\partial g_{\theta\phi}}{\partial \phi}\boldsymbol{-}\frac{\partial g_{\theta\phi}}{\partial \phi}\right)\right]\boldsymbol{=}0 \tag{10b}\label{10b}\\ \Gamma^{\theta}_{\phi\theta} & \boldsymbol{=} \Gamma^{\theta}_{\theta\phi}\boldsymbol{=}0 \tag{10c}\label{10c} \\ \Gamma^{\theta}_{\phi\phi} & \boldsymbol{=} \frac12\left[\cancelto{^{R^{-2}}}{g^{\theta\theta}}\left(\frac{\partial \cancelto{0}{g_{\theta\phi}}}{\partial \phi}\boldsymbol{+}\frac{\partial \cancelto{0}{g_{\phi\theta}}}{\partial \phi}\boldsymbol{-}\cancelto{^{2R^2\sin\theta\cos\theta}}{\frac{\partial g_{\phi\phi}}{\partial \theta}}\right)\boldsymbol{+}\cancelto{0}{g^{\theta\phi}} \left(\frac{\partial g_{\phi\phi}}{\partial \phi}\boldsymbol{+}\frac{\partial g_{\phi\phi}}{\partial \phi}\boldsymbol{-}\frac{\partial g_{\phi\phi}}{\partial \phi}\right)\right] \nonumber\\ &\boldsymbol{=}\boldsymbol{-}\sin\theta\cos\theta \tag{10d}\label{10d} \end{align} Finding also by this way the elements of $\boldsymbol{\Gamma^{\phi}}$ we have the following two $2\times 2$ symmetric matrices \begin{align} \boldsymbol{\Gamma^{\theta}}\boldsymbol{=}\Gamma^{\theta}_{\beta\nu}& \boldsymbol{=} \begin{bmatrix} 0\hphantom{r^2\theta} & \hphantom{r^2}0\hphantom{r^2\theta} \vphantom{\dfrac{a}{b}}\\ 0\hphantom{r^2\theta} & \boldsymbol{-}\dfrac{\sin2\theta}{2} \vphantom{\dfrac{a}{b}} \end{bmatrix} \tag{11a}\label{11a}\\ \boldsymbol{\Gamma^{\phi}}\boldsymbol{=}\Gamma^{\phi}_{\beta\nu}& \boldsymbol{=} \begin{bmatrix} 0 & \hphantom{r^2}\cot\theta \vphantom{\dfrac{a}{b}}\\ \cot\theta & \hphantom{r^2} 0 \vphantom{\dfrac{a}{b}} \end{bmatrix} \tag{11b}\label{11b} \end{align} But in our case $\theta\boldsymbol{=}\theta_{0}\boldsymbol{=}\pi/2$ so \begin{align} \boldsymbol{\Gamma^{\theta}}\boldsymbol{=}\Gamma^{\theta}_{\beta\nu}& \boldsymbol{=} \begin{bmatrix} 0\hphantom{r^2\theta} & \hphantom{r^2}0\hphantom{r^2\theta} \vphantom{\dfrac{a}{b}}\\ 0\hphantom{r^2\theta} & \boldsymbol{-}\dfrac{\sin2\theta}{2} \vphantom{\dfrac{a}{b}} \end{bmatrix} \stackrel{\theta=\pi/2}{\boldsymbol{=\!=\!=}} \begin{bmatrix} \: 0 & \hphantom{=}0 \:\vphantom{\dfrac{a}{b}}\\ \: 0 & \hphantom{=}0 \:\vphantom{\dfrac{a}{b}} \end{bmatrix} \tag{12a}\label{12a}\\ \boldsymbol{\Gamma^{\phi}}\boldsymbol{=}\Gamma^{\phi}_{\beta\nu}& \boldsymbol{=} \begin{bmatrix} 0 & \hphantom{r^2}\cot\theta \vphantom{\dfrac{a}{b}}\\ \cot\theta & \hphantom{r^2} 0 \vphantom{\dfrac{a}{b}} \end{bmatrix} \stackrel{\theta=\pi/2}{\boldsymbol{=\!=\!=}} \begin{bmatrix} \: 0 & \hphantom{=}0 \:\vphantom{\dfrac{a}{b}}\\ \: 0 & \hphantom{=}0 \:\vphantom{\dfrac{a}{b}} \end{bmatrix} \tag{12b}\label{12b} \end{align} and \eqref{04} yields \begin{equation} \dfrac{\mathrm d\mathbf{V}}{\mathrm d\phi} \boldsymbol{=} \begin{bmatrix} \dfrac{\mathrm dV^\theta}{\mathrm d\phi}\vphantom{\dfrac{a}{\dfrac{a}{b}}}\\ \dfrac{\mathrm dV^\phi}{\mathrm d\phi}\vphantom{\dfrac{a}{b}} \end{bmatrix} \boldsymbol{=}\boldsymbol{-} \begin{bmatrix} \Bigl< \boldsymbol{\Gamma^{\theta}}\mathbf{V},\dfrac{\mathrm d\boldsymbol{\chi}}{\mathrm d\phi}\Bigr> \vphantom{\dfrac{a}{\dfrac{a}{b}}}\\ \Bigl< \boldsymbol{\Gamma^{\phi}}\mathbf{V},\dfrac{\mathrm d\boldsymbol{\chi}}{\mathrm d\phi}\Bigr> \vphantom{\dfrac{a}{\dfrac{a}{b}}} \end{bmatrix} \boldsymbol{=} \begin{bmatrix} \:\:0\:\:\vphantom{\dfrac{\tfrac{a}{b}}{\dfrac{a}{b}}}\\ \:\:0\:\:\vphantom{\dfrac{\dfrac{a}{b}}{\tfrac{a}{b}}} \end{bmatrix} \tag{13}\label{13} \end{equation} that is \begin{equation} V^\theta\boldsymbol{=}\texttt{constant}\boldsymbol{=}V^\theta_{0}\,, \qquad V^\phi\boldsymbol{=}\texttt{constant}\boldsymbol{=}V^\phi_{0} \tag{14}\label{14} \end{equation}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.